Integration of PHC concepts in the revised DECS' BSN curriculum in selected schools in Baguio and Region I - Tingda, Ruth Thelma P.
This study determined the extent of integration of Primary Health Care concepts in the revised DECS' BSN curriculum as perceived by graduating nursing students for the school year 1992-1993 in eight nursing colleges in Baguio City and Region I. Likewise, it aimed to seek answers on the extent of importance, relevance, applicability and adequacy of PHC concepts, the overall extent of attainment of the terminal competencies, the extent of PHC concepts integrated in Levels 2, 3 and 4, the extent of effect of selected factors on PHC concepts integration, and the extent of effect of selected teaching strategies on PHC integration.The study employed a descriptive survey design. The 800 respondents were chosen by quota (100 students in each school) and clustered random sampling procedures. Questionnaire was the tool used to gather data which were later on consolidated manually by computing for the frequencies and mean scores. Inferential statistics through computer was done for the analysis of variance (ANOVA), particularly F test and further tested with DMRT or Duncan's Multiple Range Test to compare group of means of items with significant F values. The .05level of significance was used as point of reference.This study carried the following hypotheses:1. There is no significant difference in the perceptions of graduating students from the eight selected nursing schools on the extent of importance, relevance, applicability and adequacy of PHC concepts integrated in the revised DECS' BSN curriculum.2. There is no significant difference in the perceptions of graduating students from the eight selected nursing schools on the overall extent of attainment of the terminal competencies in the revised DECS' BSN curriculum.3. There is no significant difference in the perceptions of graduating students from the eight selected nursing schools on the extent of integration of PHC concepts in Levels 2, 3 and 4 of the revised DECS' BSN curriculum.4. There is no significant difference on the effect of selected factors on the integration of PHC in the revised DECS' BSN curriculum as perceived by the graduating students from the eight selected nursing schools.5. There is no significant difference in the perceptions of graduating students form the eight selected nursing schools on the effect of selected teaching strategies on PHC integration in the revised DECS' BSN curriculum.